VOCATIONAL EDUCATION STUDENTS’ PERCEPTION ON ETHICS STUDY: EVIDENCE FROM ACCOUNTING STUDENTS - Wai-Yi Cheung, Rachel (PEOPLE: International Journal of Social Sciences, 2019)
Vocational education must operate within a lifelong learning context. Accounting is a vocational study. Besides core accounting knowledge, thinking and practicing capabilities are required for an accountant while judgement with ethical consideration is an important capability. Thus, accounting students should apprehend ethics. This research aims to investigate accounting students’ perception on the importance on ethics themes which are represented by 17 keywords, students were asked to rate how important they perceive an accounting graduate should have learnt these keywords in a curriculum. The focus is on all students, further to gender and the studying year (senior and junior). Data were collected from nine higher education institutes in Hong Kong. Overall, students (n=72) rated “codes of ethics” the most important and surprisingly “independence” as second. Male (39) and female (33) rated differently in many keywords, e.g. “corruption” & “social responsibility”. The difference in rating between students at senior (34) and junior (38) years is narrow, with exception on “corruption”, “corporate governance” and “insider trading”. The findings offer an insight for educators in vocational based education to include appropriate ethics elements in accounting curriculum so to let students attain both core technical skills and skills for surviving in this ever-changing world.